2020
DOI: 10.14238/pi60.5.2020.253-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of platelet indices for neonatal bacterial sepsis

Abstract: Background Neonatal bacterial sepsis is a major cause of neonatal morbidity and mortality worldwide. Blood culture as a gold standard, as well as C reactive protein (CRP), micro erythrocyte sedimentation rate (micro ESR), white blood count (WBC), and immature-to-total (I/T) ratio as a sepsis screens are currently used methods, but their utility may be limited due to delayed reporting. Platelet indices are one of the parameters which can be helpful in the diagnosis of neonatal bacterial sepsis. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, another study from Indonesia conducted by Rohadi reported that among the cases group, the blood culture that yielded Gram-positive organisms over numbered the Gram negative ones. This may be attributed to lower gestational age and lower birth weight found in the culture proven sepsis group, lower number of cases group and difference in geographic distribution [10].…”
Section: So Our Study Aimed At Determination Of the Role Of Mpv And Plasma Lactate Level In The Diagnosis And Prognosis Of Neonatal Bactementioning
confidence: 89%
See 1 more Smart Citation
“…However, another study from Indonesia conducted by Rohadi reported that among the cases group, the blood culture that yielded Gram-positive organisms over numbered the Gram negative ones. This may be attributed to lower gestational age and lower birth weight found in the culture proven sepsis group, lower number of cases group and difference in geographic distribution [10].…”
Section: So Our Study Aimed At Determination Of the Role Of Mpv And Plasma Lactate Level In The Diagnosis And Prognosis Of Neonatal Bactementioning
confidence: 89%
“…Neonatal sepsis is commonly diagnosed by a combination of clinical signs, nonspecific laboratory tests, and microbiologically confirmed by positive blood culture [10]. Thus, there is an eager need of a biomarker that can point out sepsis in an early stage so that appropriate management plan can be started and antibiotics can be initiated [11].…”
Section: The Prognosis and Outcome Of Neonatal Sepsis Depend On Early Diagnosis And Proper Management [9]mentioning
confidence: 99%
“…The results of our study agree with those of several previous studies that revealed a significant difference in the MPV and PDW of the case group compared to the control group. [8][9][10][11] In neonatal infection, platelet production climbs in response to the elevated need for coagulation activities due to endothelial damage or increased platelet destruction; thereby, larger and younger platelets are introduced into the peripheral blood. Hence, MPV and PDW values rise in acute infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in other developing countries such as Tanzania and Indonesia have reported similar clinical signs of EONI. 7, 8 To minimize empiric antibiotic therapy, investigations of more specific and sensitive markers for the diagnosis of EONI have emerged and received huge attention from clinical neonatologists. Given the limited economic resources, equipment, and tests in most developing countries, finding a simple, useful, and inexpensive marker of neonatal infection is necessary.…”
Section: Discussionmentioning
confidence: 99%